PENDAPATAN USAHAâ€ CAP TIKUSâ€ DI DESA RANOLAMBOT KECAMATAN KAWANGKOAN BARAT (Business Income â€œCap Tikusâ€ in Ranolambot Village District of Kawangkoan Barat) - Jamal M. Buyung; Paulus A. Pangemanan; Melsje Y. Memah (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2021)
The purpose of this study was to analyze the income from the "Cap Tikus" business in Ranolambot Village, West Kawangkoan District, Minahasa. The sampling method used in this research was purposive sampling method. The number of respondents chosen was 20 people who were taken from the 5 existing local community group. The data analysis method used was income analysis.The results showed that the total revenue by all respondents in one month with 12 production of "Cap Tikus" was IDR 84,000,000.- or an average of IDR 4,200,000 per respondent. Meanwhile, the total production cost for all respondents was IDR 34,324,999.99 or an average of IDR 1,716,249.99 per respondent. Therefore, the total income for one month for all respondents was IDR 49,675,000.01 or an average of IDR 2,483,750 per respondent per month.Keywords: income, "Cap Tikus"